The Role of Ties as a Mechanism for Enhancing SMEs Adaptiveness to Economic Crises in Egypt: Evidences from Feeding Industry and Intermediary Goods Sector - Al Husseiny, Nour; Ashour, Ahmed (The Arab Journal of Administration, 2021)
The study aims at introducing a heuristic framework to explore SMEs responses during economic crises in Egypt since January 2011 revolution till 2017. Based on theories of Resource Based View and Social Capital, the framework focuses on studying the patterns of ties formation (ties broadening versus ties reinforcing) which were held between SMEs under investigation and their basic partners during the period of the study. In addition, the study investigates the comparable effects of environmental and organizational variables on the same patterns of ties formation. Furthermore, it aims to explore how the patterns of ties formation may act as a mechanism to help SMEs pursuing different adaptive strategies during economic crises. Using a purposive sample of 70 small and medium-sized enterprises, which succeeded to survive during the recession, and operating in feeding industries and intermediary goods sector, the research collected data at the end of 2017 through personal interviews and questionnaires. Using (PLS) and the related path analysis, the results indicated that both environmental variables (perceived recession related effects) and organizational variables (entrepreneurial orientation) had different effects on patterns of ties formation during the crises. Moreover, in the context of SMEs, organizational variables played a more important role in explaining patterns of ties formation Compared with environmental variables. Finally, the results revealed the important role of ties formation patterns in explaining growth strategy pursued by SMEs to survive under economic crises. Overall, the study contributed to understanding SMEs responses during recessions, especially in Egypt and generally in developing economies facing crises, and shed light on the usefulness of ties as a mechanism used to facilitate adaptiveness of SMEs during drastic environmental shocks. Beased on study results and suggestions, the study introduced a framework that may guide future research.